Economics of Public Antibiotics Development - Okhravi, Christopher (Frontiers in Public Health, 2020)
Issuing monetary incentives, such as market entry rewards, to stimulate private firm engagement has been championed as a solution to our urgent need for new antibiotics, but we ask whether it is economically rational to simply take public ownership of antibiotics development instead. We show that the cost of indirectly funding antibiotics development through late phase policy interventions such as market entry rewards may actually be higher than simple direct funding. This result is reached by running a Monte Carlo simulation comparing the cost of increasing the ratio of investment go-decisions at the outset of pre-clinical development, to the cost of directly funding the same antibiotics under various levels of operational inefficiency. We simulate costs for hypothetical antibiotics targeting six different indications, using data from previous studies. We conclude that while indirect funding may be necessary for the current pipeline we may want to prefer direct funding as a cost effective long-term solution for future antibiotics.